2009
DOI: 10.1007/s10450-009-9199-0
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of carbon molecular sieves from palm shell: effect of benzene deposition conditions

Abstract: Application of carbon molecular sieve (CMS) for gas separation has been found much attention recently. In this work, CMS was prepared from locally available palm shell through carbonization, steam activation and carbon vapour deposition (CVD) technique. After carbonization step, the char produced was subjected to steam activation at various activation times. The activated carbon obtained at 53.2% burn-off, which contain the highest amount of micropore volume was further used in CVD step by using benzene vapour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…222,223 It can be prepared from any inexpensive carbonaceous material with low inorganic compounds such as lignocellulosic materials, biomass and coal by pyrolyzation, covering, and carbon deposition methods. [222][223][224][225][226][227][228][229][230][231][232] The chemical vapor deposition (CVD) method utilizes carbon deposition agents such as acetylene, 233 benzene, 221,229,234 methylpentane, 227 cyclohexane, 229 and methane 235,236 either in liquid or vapor form for pyrolytic carbon deposition at pore mouth to match the pore entrance with the adsorbate size. 220 The advantage of using CMS-based CO 2 adsorbent is its versatile selectivity for gas molecule separation with different molecular sizes.…”
Section: Carbon Molecular Sievementioning
confidence: 99%
See 1 more Smart Citation
“…222,223 It can be prepared from any inexpensive carbonaceous material with low inorganic compounds such as lignocellulosic materials, biomass and coal by pyrolyzation, covering, and carbon deposition methods. [222][223][224][225][226][227][228][229][230][231][232] The chemical vapor deposition (CVD) method utilizes carbon deposition agents such as acetylene, 233 benzene, 221,229,234 methylpentane, 227 cyclohexane, 229 and methane 235,236 either in liquid or vapor form for pyrolytic carbon deposition at pore mouth to match the pore entrance with the adsorbate size. 220 The advantage of using CMS-based CO 2 adsorbent is its versatile selectivity for gas molecule separation with different molecular sizes.…”
Section: Carbon Molecular Sievementioning
confidence: 99%
“…In addition to its low CO 2 adsorption capacity, the CMS is not favored as a CO 2 adsorbent due to its high toxicity and high cost of depositing agents. 236,241 It can also generate intermediates during the deposition process 220,233,236 and the CO 2 adsorption performance is dependent on the pyrolytic reaction or carbon deposition conditions. 221,242 Layered anionic clays Layered double hydroxides (LDHs) are classified as synthetic anionic clays.…”
Section: Carbon Molecular Sievementioning
confidence: 99%
“…It was observed that the experimental values obtained were in good agreement with the values predicted from the models, with relatively small errors between the predicted and the actual values, which was only 3.05% and 1.61%, for CO 2 permeance and C0 2/CH 4 permselectivity, respectively. high thermai and chemical stability [1], Furthermore, eMS membranes are amorphous in nature, In addition, CMS membranes are tougher and more flexible [2], For gas separation process, the membranes needs to exhibit molecular sieving capabilities with pore size near the dimension of gas molecules to be separated [3], CMS membranes contain a thin carbon layerhaving pores with a size smallerthan 1nm, which allowthe gases separation such as oxygen (0,) and nitrogen (N,) from air [4], Pure 0, is widely used for medical purposes while pure N, is used for blanketing perishable fruits and also for shipment offlammable liquids, Suda and Haraya [5] pyrolyzed Kapton polyimlde at 800"C and obtained CMS membrane As the pyrolysis temperature increases, the surface area and pore volume decreases. Sample CMS700 shows narrower FSD at approximately 0.41 nm compared to CMS800 and CMS900 as shown in The porous membrane support was made by blending phenolic resin (60%) and carbon black (30%) together with cellulose acetate (10%) as binder.…”
Section: Criteria Was Set As Maximum Values For the Two Responses While The Values Of The Three Variablesmentioning
confidence: 99%
“…CMS membrane is prepared from the controlled pyrolysis of polymeric precursor. Its microstructure resembles the basic structure of the polymers but with much superlor selectivity, thermal stability and strength [3]. As result, gas molecules with very similar diameter can be efficiently separate by CMS membrane under normal operation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon molecular sieve (CMS) membranes have received much attention for gas separation due to its superior gas permeation performance as well as high thermai and chemical stability [1], Furthermore, eMS membranes are amorphous in nature, In addition, CMS membranes are tougher and more flexible [2], For gas separation process, the membranes needs to exhibit molecular sieving capabilities with pore size near the dimension of gas molecules to be separated [3], CMS membranes contain a thin carbon layerhaving pores with a size smallerthan 1nm, which allowthe gases separation such as oxygen (0,) and nitrogen (N,) from air [4], Pure 0, is widely used for medical purposes while pure N, is used for blanketing perishable fruits and also for shipment offlammable liquids, Suda and Haraya [5] pyrolyzed Kapton polyimlde at 800"C and obtained CMS membrane As the pyrolysis temperature increases, the surface area and pore volume decreases. Sample CMS700 shows narrower FSD at approximately 0.41 nm compared to CMS800 and CMS900 as shown in The porous membrane support was made by blending phenolic resin (60%) and carbon black (30%) together with cellulose acetate (10%) as binder.…”
Section: Introductionmentioning
confidence: 99%